Análise do movimento do móvel usando o trilho de ar e a placa arduino como aquisição de dados - Cavalcanti, Deiverson Rodrigo Candido (2016)
The objective of this work is to propose a new pedagogical teaching practice, with the purpose of seeking a greater interest of the students by the teaching of sciences, mainly in Physics. The work consists of a few steps, performing experiments using an experimental prototype called Motion Analysis Using the Air Rail and the Arduino Plate. In that prototype, it uses LDR sensors connected to the Arduino board in order to make the temporary marking of the trolley by moving on the air rail. The area of the chosen physics was the kinematics, specifying more the contents of uniform rectilinear movement and uniformly varied rectilinear motion, subjects that cause many doubts in the understanding and the distinction of these two movements. Two experimental activities will be proposed to the students, one of MRU and another of MRUV in which the two are limited to putting the cart in motion on the air rail, to make the temporal marking through the sensors in the interface of Arduino, to calculate the speed and to observe If it is constant in the first experiment, calculate the scalar acceleration for two different slopes and verify if it is constant in the two cases and propose to the students the construction and a greater understanding in the kinematics graphs. It is hoped that this experimental prototype will be a very important and useful tool in physics classes.